2020
DOI: 10.1002/ana.25684
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Biomarkers of Alzheimer Disease in Multiple Sclerosis

Abstract: Objective To investigate β‐amyloid and tau depositions using Pittsburgh compound B (PiB) positron emission tomography (PET) and AV1451 tau PET imaging in aging multiple sclerosis (MS) patients. Methods Patients with MS (n = 16) and controls (n = 80) matched for age, sex, and APOE ε4 status from the population‐based Mayo Clinic Study of Aging who underwent PiB PET imaging were studied. Of these individuals, 12 patients with MS and 60 matching controls also underwent AV1451 tau PET. Cortical PiB and AV1451 stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Although aggregation of oligomeric Aβ (oAβ) and plaques formation is a major feature of AD (53), soluble oAβ, particularly those encompassing Aβ 1−42 , are neurotoxic (54). On the other hand, in MS despite the augmented expression of the amyloid precursor protein (APP), reflecting axonal damage (55,56), and the increased levels of soluble α-APP and β-APP, intermediate products of APP proteolysis, in brain lesions (57), amyloid plaques have not been found (58)(59)(60)(61)(62). The latter could reflect an enhanced demyelinization and release of myelin basic protein, as this protein inhibits amyloid fibril formation (favoring the detrimental effect of their soluble precursors) (63)(64)(65)(66) and/or their enhanced cleaning due to microglial activation (62).…”
Section: Nci and Histopathological Signature Of Ms And Admentioning
confidence: 99%
“…Although aggregation of oligomeric Aβ (oAβ) and plaques formation is a major feature of AD (53), soluble oAβ, particularly those encompassing Aβ 1−42 , are neurotoxic (54). On the other hand, in MS despite the augmented expression of the amyloid precursor protein (APP), reflecting axonal damage (55,56), and the increased levels of soluble α-APP and β-APP, intermediate products of APP proteolysis, in brain lesions (57), amyloid plaques have not been found (58)(59)(60)(61)(62). The latter could reflect an enhanced demyelinization and release of myelin basic protein, as this protein inhibits amyloid fibril formation (favoring the detrimental effect of their soluble precursors) (63)(64)(65)(66) and/or their enhanced cleaning due to microglial activation (62).…”
Section: Nci and Histopathological Signature Of Ms And Admentioning
confidence: 99%
“…30 Furthermore, a recent study using PET imaging biomarkers of AD even suggested that some aspects of MS pathobiology retard the accumulation of β-amyloid, which is one of the main pathologic correlates of AD. 31 Nevertheless, we cannot exclude the possibility that patients with APOE e4 homozygosity performed worse in the cognitive tests because of an APOE e4-mediated increased risk of developing MCI or AD.…”
Section: Discussionmentioning
confidence: 94%
“…Two recent studies have examined the association between amyloid PET tracer binding and cognitive function in MS [ 11 , 21 ], and a prospective population-based study used amyloid PET to investigate beta-amyloid accumulation in ageing MS patients and matched controls [ 20 ]. Yet, there are no reports of API to diagnose AD in patients with established MS and increasing cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%